Utilization of Banana as a Raw Material for Cracker Manufacturing - Madu, Konstantinus; Mush, Wahyu; Rahmawati, Atina (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2024)
Banana fronds have a porous, hollow and fibrous character so their density value is large. Apart from that, banana stems contain more than 50% cellulose. People generally don't pay much attention to banana stems, especially after the tree bears fruit. Therefore, this research attempts to make crackers using Kepok banana leaves as raw material. Hopefully that this research will produce crackers made from banana stems. This research aims to determine the effect of adding banana gedebog, wheat flour on crackers' physical, chemical, and organoleptic quality and the business feasibility analysis of making crackers with the best treatment results. This research aims to determine the effect of adding banana gedebog, and wheat flour on crackers' physical, chemical, and organoleptic quality and the business feasibility analysis of making crackers with the best treatment results. The design used in this research was a Completely Randomized Design (CRD), with 5 treatment combinations whose formulations were: F1 = 70% gedebog banana + 20% wheat flour; F2 = 60% banana banana + 30% wheat flour; F3 = 50% banana gebog + 40% wheat flour; F4 = 40% banana gebog + 50% wheat flour, and; F5 = 30% banana gebog + 60% wheat flour, then each treatment was repeated 3 (three) times to obtain 15 samples. The results showed that the best treatment was found in F2 (60% gedebog flour; 30% wheat flour and 10% tapioca flour with chemical content in the form of: 4.25% moisture content; 15.59% crude fiber; 1.12% organoleptic test; taste preference 3.67 (very like); aroma 3.57 (like), and; color 3.55 (like). Based on the feasibility analysis, manufacturing banana stem crackers based on the best treatment is feasible.